The stage manager's toolkit : templates and communication techniques to guide your theatre production from first meeting to final performance - Kincman, Laurie (New York : Routledge, 2021)
"The Stage Manager's Toolkit Third Edition provides a comprehensive account of the role of the stage manager for live theatre with a focus on both written and verbal communication best practices. The book outlines the duties of the stage manager and assistant stage manager throughout a production, discussing not only what to do but why. It also identifies communication objectives for each phase of production, paperwork to be created, and the necessary questions to be answered in order to ensure success. This third edition includes: - an updated look at digital stage management tools including script apps, cloud storage, and social media practices; - a new discussion on creating a healthy and safe rehearsal space; - updated paperwork examples; - new information on Equity practices for the student and early career stage managers. Written for the stage management student and early career stage manager, this book is a perfect companion to any university Stage Management course. A companion website hosts customizable paperwork templates, instructional video, links to additional information, teacher tools for each individual chapter, and a bonus chapter on teaching stage management"--
P.B
Includes bibliographical references and index.
Keywords: Stage management